Prognostic factors of congenital diaphragmatic hernia accompanied by cardiovascular malformation. Issue 4 (5th August 2013) - Takahashi, Shigehiro; Sago, Haruhiko; Kanamori, Yutaka; Hayakawa, Masahiro; Okuyama, Hiroomi; Inamura, Noboru; Fujino, Yuji; Usui, Noriaki; Taguchi, Tomoaki
Abstract: Background: Congenital diaphragmatic hernia is associated with cardiovascular malformation. Many prognostic factors have been identified for isolated congenital diaphragmatic hernia; however, reports of concurrent congenital diaphragmatic hernia and cardiovascular malformation in infants are limited. This study evaluated congenital diaphragmatic hernia associated with cardiovascular malformation in infants. Factors associated with prognosis for patients were also identified. Methods: This retrospective cohort study was based on a Japanese survey of congenital diaphragmatic hernia patients between 2006 and 2010. Frequency and outcome of cardiovascular malformation among infants with congenital diaphragmatic hernia were examined. Severity of congenital diaphragmatic hernia and cardiovascular malformation were compared as predictors of mortality and morbidity. Results: Cardiovascular malformation was identified in 76 (12.3%) of 614 infants with congenital diaphragmatic hernia. Mild cardiovascular malformation was detected in 19 (33.9%) and severe cardiovascular malformation in 37 (66.1%). Their overall survival rate at discharge was 46.4%, and the survival rate without morbidity was 23.2%. Mortality and morbidity at discharge were more strongly associated with severity of cardiovascular malformation (adjusted OR 7.69, 95%CI 1.96–30.27; adjusted OR 7.93, 95%CI 1.76−35.79, respectively) than with severity of congenital diaphragmatic hernia. Conclusions: The prognosis for infants with both congenital diaphragmatic hernia and cardiovascular malformation remains poor. Severity of cardiovascular malformation is a more important predictive factor for mortality and morbidity than severity of congenital diaphragmatic hernia.